Adenovirus Modulates Toll-Like Receptor 4 Signaling by Reprogramming ORP1L-VAP Protein Contacts for Cholesterol Transport from Endosomes to the Endoplasmic Reticulum - Cianciola, Nicholas L. (J Virol, 2017)
Human adenoviruses (Ads) generally cause mild self-limiting infections but can lead to serious disease and even be fatal in high-risk individuals, underscoring the importance of understanding how the virus counteracts host defense mechanisms. This study had two goals. First, we wished to determine the molecular basis of cholesterol homeostatic responses induced by the early region 3 membrane protein RIDα via its direct interaction with the sterol-binding protein ORP1L, a member of the evolutionarily conserved family of oxysterol-binding protein (OSBP)-related proteins (ORPs). Second, we wished to determine how this interaction regulates innate immunity to adenovirus. ORP1L is known to form highly dynamic contacts with endoplasmic reticulum-resident VAP proteins that regulate late endosome function under regulation of Rab7-GTP. Our studies have demonstrated that ORP1L-VAP complexes also support transport of LDL-derived cholesterol from endosomes to the endoplasmic reticulum, where it was converted to cholesteryl esters stored in lipid droplets when ORP1L was bound to RIDα. The virally induced mechanism counteracted defects in the predominant cholesterol transport pathway regulated by the late endosomal membrane protein Niemann-Pick disease type C protein 1 (NPC1) arising during early stages of viral infection. However, unlike NPC1, RIDα did not reconstitute transport to endoplasmic reticulum pools that regulate SREBP transcription factors. RIDα-induced lipid trafficking also attenuated proinflammatory signaling by Toll-like receptor 4, which has a central role in Ad pathogenesis and is known to be tightly regulated by cholesterol-rich “lipid rafts.” Collectively, these data show that RIDα utilizes ORP1L in a way that is distinct from its normal function in uninfected cells to fine-tune lipid raft cholesterol that regulates innate immunity to adenovirus in endosomes. IMPORTANCE Early region 3 proteins encoded by human adenoviruses that attenuate immune-mediated pathology have been a particularly rich source of information regarding intracellular protein trafficking. Our studies with the early region 3-encoded RIDα protein also provided fundamental new information regarding mechanisms of nonvesicular lipid transport and the flow of molecular information at membrane contacts between different organelles. We describe a new pathway that delivers cholesterol from endosomes to the endoplasmic reticulum, where it is esterified and stored in lipid droplets. Although lipid droplets are attracting renewed interest from the standpoint of normal physiology and human diseases, including those resulting from viral infections, experimental model systems for evaluating how and why they accumulate are still limited. Our studies also revealed an intriguing relationship between lipid droplets and innate immunity that may represent a new paradigm for viruses utilizing these organelles.